2020
DOI: 10.1186/s12936-020-03178-9
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the deletion in the pfhrp2 and pfhrp3 genes in Plasmodium falciparum from Equatorial Guinea

Abstract: Background: The World Health Organization (WHO) recommends rapid diagnostic tests (RDTs) as a good alternative malaria-diagnosis method in remote parts of sub-Saharan Africa. The majority of commercial RDTs currently available detect the Plasmodium falciparum protein histidine-rich protein 2 (PfHRP2). There have also been recent reports of pfhrp2 gene deletions being found in parasites collected from several African countries. The WHO has concluded that lacking the pfhrp2 gene must be monitored in Africa. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…By contrast, reports of presence of pfhrp2 gene deletions in West Africa have been limited, including in Mali 12 and Senegal 13 . Recent studies provide evidence of deletion of the pfhrp2 gene as reported from Equatorial Guinea 26 and Nigeria 27 . However, in many highly malaria-endemic countries, data about pfhrp2 deletion are missing.…”
Section: Discussionmentioning
confidence: 79%
“…By contrast, reports of presence of pfhrp2 gene deletions in West Africa have been limited, including in Mali 12 and Senegal 13 . Recent studies provide evidence of deletion of the pfhrp2 gene as reported from Equatorial Guinea 26 and Nigeria 27 . However, in many highly malaria-endemic countries, data about pfhrp2 deletion are missing.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, a recent study in Ghana reported pfhrp2 gene deletion in 33 and 36% of microscopicallyconfirmed and PCR-confirmed RDT positive samples, respectively [21]. Over the past decade, several countries, especially in Africa, have reported cases of P. falciparum isolates with deleted pfhrp2, and isolates with high pfhrp2 diversity [17,18,[22][23][24][25][26], with potential negative implications for malaria control and elimination programmes. These notwithstanding, studies on pfhrp2 gene deletion and diversity of the pfhrp2 gene in Ghana, a malaria-endemic country, are lacking.…”
mentioning
confidence: 99%
“…HRP 2 deletions were also identified in Honduras and Peru with a 40.6% deletion rate identified in Iquitos, Peru, which makes HRP2 a poor option in that region [ 13 , 23 ]. From 2019–2020, Pf- HRP 2 and HRP3 mutations were reported in 15 countries and confirmed in 11 countries, including: China, Equatorial Guinea, Ethiopia, Ghana, Myanmar, Nigeria, Sudan, Uganda, United Kingdom (imported), Tanzania, Zambia [ 2 , 24 ]. As such, the WHO has recommended that countries with PfHRP2/3 deletions and neighboring countries should “conduct baseline surveys among suspected malaria cases” to determine whether there is a greater than 5% HRP2 deletion rate resulting in false negatives [ 2 ].…”
Section: Limitation: Genetic Variationmentioning
confidence: 99%